Influencia de la concentración inicial de azúcares y la temperatura de fermentación en el rendimiento de un bioplástico a partir del hidrolizado de granos usados de cervecería empleando pseudomonas aeruginosa. - Fuentes Olivera, Anthony Jeams (2015)
The biosynthesis of polyhydroxyalkanoate by Pseudomonas aeruginosa grown on reducing sugar hydrolysate obtained from brewer spend grain as the sole carbon source and sodium sulphate as the limiting nutrient was investigated. This involved hydrolysis of hemicellulose from brewer spend grain using dilute acid method of hydrolysis, followed by aerobic fermentation of Pseudomonas aeruginosa on a mixture of the hydrolysate and nutrient media in batch cultures. The biomass growth was measured by cell dry weight and the polyhydroxyalkanoate content measured by molecular spectrophotometry. The temperature of fermentation and the initial substrate concentration were studied. The results obtained show that the hydrolysate supported the growth of the organism, the best temperature and initial substrate concentration were 30 °C and 20 g/L of reducing sugar concentration from biomass yield in substrate (Y x/s) of 0.23 g g-1. However, the best temperature and initial substrate concentration were 30 °C and 10 g/L of reducing sugar concentration from the organism to accumulated polyhydroxyalkanoate giving a final polyhydroxyalkanoate yield on biomass (Y p/x) of 0.005 g g-1 which are low yield in polyhydroxyalkanoate production probably because hydrolysate inhibitors and a low use of pentose as a carbon source by Pseudomonas aeruginosa.